(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: The unprecedented global pandemic caused by SARS-CoV-2 creates considerable psychological problems among the health care workers (HCW). The present study aimed to determine the predictors of psychological impact (in terms of depression, anxiety and stress) among the HCWs exposed Covid-19 cases in Combined Military Hospital (CMH) Dhaka. Methods: This cross-sectional study was conducted at CMH Dhaka among purposively selected 390 HCWs. Data were collected through face-to-face interview using a pre-tested semi-structured questionnaire with validated and reliable tools. The study was conducted in the Combined Military Hospital Dhaka from 15 July 2020 to 30 September 2020. Results: Among the 390 respondents, 21.6%, 43.1% and 24.1% had depression, anxiety and stress symptoms, respectively. Being married (OR=0.391, 95% CI=0.160-0.953), graduate (OR=2.977; 95% CI=1.181-7.509) and attending 41-80 patients per day (OR=1.996; 95% CI=0.965-4.125) was significantly associated with depressive symptoms. In respect of anxiety, being graduate (OR=2.788, 95% CI=1.228 -6.333) and HSC qualified (OR=2.714, 95% CI=1.073-6.869), staying in family accommodation (OR=2.720, 95% CI=1.136 - 6.516), with nuclear family (OR=0.459, 95% CI=0.281-0.750), smoker (OR=1.827, 95% CI=0.987 - 3.384), doctor (OR=0.362, 95% CI=0.173- 0.758), having service length <20 years (OR=2.229, 95% CI=1.158 - 4.289), service in current place of posting for <20 months (OR=0.460, 95% CI=0.241-0.880), attended 41-80 patient daily (OR=1.720, 95% CI=0.933 - 3.169) and performing overtime duty (OR=2.568, 95% CI=1.609-4.099) were significantly associated with anxiety symptoms. Being graduate (OR=2.249, 95% CI=0.866-5.844), with nuclear family type (OR=0.423, 95% CI=0.249-0.721), having duty place at emergency (OR=2.135, 95% CI=0.902-5.053), being a nurse (OR=0.364, 95% CI=0.162-0.819), having service length <10 years (OR=2.570, 95% CI=1.207-5.472) and performing overtime duty (OR=2.214, 95% CI=1.3101-3.742) were significantly associated with stress symptoms. Conclusion: Psychological problems among the HCW found very common in our study which needs psychological crisis interventions to protect the mental health of HCWs. JOPSOM 2021; 40(1): 1-13